Experimental and numerical study of lift-off length and ignition delay of a two-component diesel surrogate. (15th October 2015) - Payri, Raúl; Viera, Juan Pablo; Pei, Yuanjiang; Som, Sibendu
Highlights: Robust validation of the simulation against experimental data for wide range of conditions. Reduced chemical kinetic mechanism for multi-component surrogate available for engine simulations. Ignition delay and LOL of an ECN injector are measured with ECN standard diagnostics and ECN-suggested diesel surrogate. A sweep of injection pressure, ambient density and ambient temperature has been performed. Abstract: Understanding and controlling mixing and combustion processes is fundamental for the ever more demanding pollutant regulations and fuel consumption standards of direct injection diesel engines. The fundamentals of these processes have been long studied from both experimental and numerical perspectives. As numerical models become more advanced, the need for adequate experimental data increases. Hence, experimental methodologies and scientific databases need to be enhanced with more quantitative, accurate, consistent, and reliable information in order to evaluate the models in a robust fashion. The present study seeks to enhance the current state-of-the-art by further evaluating the combustion performance of a two-component diesel surrogate for multi-dimensional compression ignition engine simulations, composed of n-dodecane and m-xylene. This surrogate is expected to better represent diesel fuel combustion than the standard Engine Combustion Network (ECN) fuel (n-dodecane), since it contains an alkyl-benzene which represents an important chemical class present in diesel fuels. Experiments and numerical simulations have been performed on lift-off length and ignition delay in a wide range of conditions for a single-hole injector from ECN. The experiments were carried out in a constant-pressure flow facility able of reproducing engine-like thermodynamic conditions. The experiments focused in characterizing the ignition delay through the Schlieren technique, and the lift-off length through OH ∗ chemiluminescence visualization, at ECN suggested test conditions. On the other hand, computational fluid dynamics (CFD) simulations were performed using a multi-flamelet representative interactive flamelet (mRIF) model by taking consideration of turbulence–chemistry-interaction (TCI) with a beta-function on the form of scalar probability density functions (PDFs). This model is evaluated extensively over a wider range of parametric variations in this study. Encouraging results were obtained compared to the experiments with regards to the predictions of ignition delay and lift-off length at different ambient temperatures, ambient densities and fuel-injection pressures. Under predictions were found at less reactive conditions, which leave room for improvement in the future.